'It's nice to think somebody's listening to me instead of saying "oh shut up"'. People with dementia reflect on what makes communication good and meaningful. Issue 2 (29th September 2019) - Alsawy, Sarah; Tai, Sara; McEvoy, Phil; Mansell, Warren
Accessible summary: What is known on the subject?: People with dementia experience cognitive decline which can affect their ability to communicate with others and consequently getting their needs met. Loneliness and social isolation are associated with depression and anxiety, while difficulties communicating may magnify such difficulties. Enhancing meaningful interactions may support maintenance of valued relationships and positive wellbeing. Although previous research has examined communicative experiences, this has been from the perspectives of professionals or caregivers. Exploring meaningful communication from the perspectives of people with dementia is crucial in supporting relationships and wellbeing. What the paper adds to existing knowledge?: People with dementia can be active participants in research. They are aware of their cognitive impairments as well as social interactions and features constituting meaningful communications. People with dementia recognized carers' attempts to understand and empathize with them; allowing them to feel valued and heard, empowering them to maintain interactions. Alternatively, feeling dismissed, inferior or pressured to provide 'correct' responses deterred them from further conversations. What are the implications for practice?: People with dementia have an awareness of their relationships, communications and preferences. Thus, it is imperative to respect this population and make attempts to understand their communication as they sense this effort even when miscommunications occur. Embrace qualities that facilitate person‐centred care within communications is vital as this can preserve valued relationships, support one's needs and enhance wellbeing. Such features include active listening, empathizing, being physically and mentally present, spending time to know the individual and sharing experiences, thoughts and emotions. Abstract: Introduction: Social isolation can be problematic for people with dementia; understanding what makes communication meaningful may reduce such risk. Scientific rationale: Previous research has examined caregivers' or professionals' experiences of meaningful communication. Understanding this from the perspectives of people with dementia could enhance their interactions and wellbeing. Aim: Exploring what makes communication meaningful from the perspective of people with dementia. Methods: Nine dyadic interactions between a person with dementia and a family carer were filmed. Individuals with dementia watched the footage and reflected on their communications in semi‐structured interviews. Results: Three superordinate themes emerged. Themes 'sharing moments of emotional connection' and 'empowering one's ability to communicate' related to the experience of feeling connected, understood, valued and heard, allowing further communication. Conversely, 'inhibitors to communication' related feeling disempowered and reduced interactions. Discussion: Even when carers could not understand what people with dementia attempted to communicate, their efforts to interact with them were valued and considered meaningful as they reinforce their sense of connectedness. Implications for practice: Embracing a person‐centred approach by actively attuning to the person and continuously attempting to empathize and understand persons with dementia can help preserve important relationships and allow the person to feel valued and interpersonally connected.